Integrasi Aplikasi Kolaborasi untuk Kantor Virtual - Basuki Winoto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
Latest technology leads people to be more creative in any aspect including changes on workingbehaviour. It automates office so that workers can commute in their productive time. Those workers can nowcomplete their tasks from virtual office system. Virtual office system will never be complete without the role ofcollaborative software. By the use of collaborative software, people may communicate, share their idea andwork collaborative.keyword: office, automate, virtual, commute, collaborative